Longitudinal plasma metanephrines preceding pheochromocytoma diagnosis: a retrospective case–control serum repository study. Issue 3 (March 2016) - Olson, S W; Yoon, S; Baker, T; Prince, L K; Oliver, D; Abbott, K C
Abstract : Objective: Plasma metanephrines (PMN) are highly sensitive for diagnosis of pheochromocytoma, but the natural history of PMN before pheochromocytoma diagnosis has not been previously described. The aim of the study was to compare the progression of PMN before pheochromocytoma diagnosis to matched healthy and essential hypertension disease controls. Design: A retrospective case–control Department of Defense Serum Repository (DoDSR) study. Methods: We performed a DoDSR study that compared three longitudinal pre-diagnostic PMN for 30 biopsy-proven pheochromocytoma cases to three longitudinal PMN for age, sex, race, and age of serum sample matched healthy and essential hypertension disease controls. Predominant metanephrine (MN) or normetanephrine (NMN) production was identified for each case and converted to a percentage of the upper limit of normal to allow analysis of all cases together. PMN were measured by Quest Diagnostics. Results: The predominant plasma metanephrine (PPM) was >100 and 300% of the upper limit of normal a median of 6.6 and 4.1 years before diagnosis respectively. A greater percentage of pheochromocytoma patients had a PPM >100 and >300% of the upper limit of normal compared with combined healthy and essential hypertension disease controls <2, 2–8, and >8 years prior to diagnosis. For patients with a baseline PPM 90–300% of the upper limit of normal, a 25% rate of rise per year was 100% specific for pheochromocytoma. Conclusions: PPMs elevate years before diagnosis which suggests that delayed diagnoses are common. For mild PMN elevations, follow-up longitudinal PMN trends may provide a highly specific and economical diagnostic tool.